Scrotal Swelling and Testicular Atrophy due to Schistosomiasis in a 9-Year-Old Boy: A Case Report - Peter F. Rambau; Alphonce Chandika; Philipo L. Chalya; Kahima Jackson (Case Reports in Infectious Diseases)
Schistosomiasis is a communicable disease which commonly involves urinary bladder causing hematuria, or large bowel causing bloody stool. The common species encountered in this lake region surrounding Lake Victoria in Tanzania are Schistosoma haematobium and Schistosoma mansoni. Complications can lead to portal hypertension due portal fibrosis in liver, and fibrosis in lung can lead to pulmonary hypertension; this commonly seen with S. mansoni. Major complications of S. maeametobium are chronic cystitis with squamous metaplasia with subsequent development of squamous cell carcinoma. Involvement of spinal cord causing paraplegia has been observed in S. haematobium. Other unusual pathology of schistosomiasis has been described, such as involvement of the appendix, ovary, prostate, and cervix. Here, we present a case of schistosomiasis in a 9-year-old boy who presented with left scrotal pain for one year which was accompanied by scrotal swelling; surgical exploration was done, and the finding was hydrocele and atrophic testes with nodules on the surface. Histological examination reveals atrophic testis and heavy active granulomatous inflammation with schistosoma eggs consistent with Schistosoma haematobium in the tunica vaginalis.